2014
DOI: 10.1002/jbm.a.35130
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroinvestigation of bacteria-osteoblast competition on oxygen plasma-modified PEEK

Abstract: Polyetheretherketone (PEEK) films were oxygen plasma treated to increase surface free energy and characterized by X-ray photoelectron microscopy, atomic force microscopy, and water contact angles. A parallel plate flow chamber was used to measure Staphylococcus epidermidis, Staphylococcus aureus, and U-2 OS osteosarcomal cell-line adhesion to the PEEK films in separate monocultures. In addition, bacteria and U-2 OS cells were cocultured to model competition between osteoblasts and contaminating bacteria for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
4
14
1
1
Order By: Relevance
“…Contrary to this finding Subbiahdoss et al showed that cell death occurred irrespective of the concentration of surrounding bacteria . According to Rochford et al S. aureus in concentration of 10 4 CFU/mL produced the death of osteoblast in 10 h. However, in our study a high percentage of the cells were alive after 48 h. S. aureus is an aggressive pathogen, which actively releases cytotoxic products into the surrounding environment inducing apoptosis in osteoblasts. Alexander et al proposed that S. aureus ‐induced apoptosis of osteoblasts involves activation of caspase‐8, which is an initiator caspase activated in death receptor‐mediated apoptosis pathways .…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Contrary to this finding Subbiahdoss et al showed that cell death occurred irrespective of the concentration of surrounding bacteria . According to Rochford et al S. aureus in concentration of 10 4 CFU/mL produced the death of osteoblast in 10 h. However, in our study a high percentage of the cells were alive after 48 h. S. aureus is an aggressive pathogen, which actively releases cytotoxic products into the surrounding environment inducing apoptosis in osteoblasts. Alexander et al proposed that S. aureus ‐induced apoptosis of osteoblasts involves activation of caspase‐8, which is an initiator caspase activated in death receptor‐mediated apoptosis pathways .…”
Section: Discussioncontrasting
confidence: 92%
“…Critical in the healing response of the host is the spread and proliferation of osteoblast cells on the implant surface even in presence of contamination . In our study, the presence of S. aureus diminished osteoblast adherence and viability and, as in other studies, the number and spreading area per cell decreased with increasing density of adhering staphylococci .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, in the presence of S. aureus contamination, cell death of the U-2 OS occurred within 10 h on all surfaces. Therefore, they concluded oxygen plasma-treated PEEK may be a promising way to improve implant surface free energy for better osseointegration without leading to more bacteria adhesion [68].…”
Section: Surface Free Energymentioning
confidence: 97%
“…Furthermore, biomaterials have also been found on which low levels of contaminating bacteria counter‐intuitively stimulate adhesion and spreading of tissue cells. These observations were made on widely different materials, ranging from modified titanium alloy to oxygen plasma‐modified polyetheretherketone films when osteosarcomal cells were grown in presence of contaminating S. epidermidis and suggest that cells have an intrinsic mechanism to their disposal that allows them to deal effectively with low levels of bacterial contamination on an implant surface.…”
Section: Introductionmentioning
confidence: 93%